2019
DOI: 10.1021/acsami.8b18434
|View full text |Cite
|
Sign up to set email alerts
|

Critical Features for Mesoporous Silica Nanoparticles Encapsulated into Erythrocytes

Abstract: Mesoporous silica nanoparticles (MSNs) hold great potential as a versatile platform for biomedical applications, especially drug delivery. However, evidence shows that MSNs even when PEGylated are rapidly cleared from the bloodstream by the monocyte phagocytic system. Erythrocytes, also called red blood cells (RBCs), can serve as biocompatible carriers of various bioactive substances, including drugs, enzymes, and peptides. In this work, we synthesize a series of fluorescent PEGylated MSNs with different synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…While most light-based RBC-derived constructs use the RBC membrane as a substrate coating, there are a growing number of constructs that use the RBC as a carrier. Constructs that use the RBC as a carrier can have a variety of optical cargos, including organic molecules [50][51][52] and NPs made from various metals [18] or semiconductors [53,54]. While constructs that use the RBC membrane as a coating primarily use sonication Constructs that employ RBC membranes as a substrate coating have also been shown to be stable, with many constructs showing minimal changes in size after storage of up to one week [42,43].…”
Section: Constructs That Use the Rbc As A Carriermentioning
confidence: 99%
“…While most light-based RBC-derived constructs use the RBC membrane as a substrate coating, there are a growing number of constructs that use the RBC as a carrier. Constructs that use the RBC as a carrier can have a variety of optical cargos, including organic molecules [50][51][52] and NPs made from various metals [18] or semiconductors [53,54]. While constructs that use the RBC membrane as a coating primarily use sonication Constructs that employ RBC membranes as a substrate coating have also been shown to be stable, with many constructs showing minimal changes in size after storage of up to one week [42,43].…”
Section: Constructs That Use the Rbc As A Carriermentioning
confidence: 99%
“…After modification with HA-conjugated dioleoyl phosphoethanolamine (HA-DOPE), the particle size increased to 220 nm (Additional file 1 : Figure S1A). The increase in the negative charge of RBCm-LCNPs relative to non-coated LCNPs improved nanoparticle stability in the blood [ 28 , 29 ]. LCNPs appeared round, showed uniform morphology and distribution, and were non-adhesive.…”
Section: Resultsmentioning
confidence: 99%
“…Chen found that hemolytic activity of unmodified MSNs was higher than PEGylated MSN. This result indicated that PEGylation played an important role not only in enhancing the stability of MSNs but also in reducing significant hemolysis [129] . Liu 's study showed that RBC treated by PEG-MSNs had no visible hemolysis, and their hemolysis value was nearly 20 times lower than unmodified MSNs.…”
Section: Hemocompatibility Characteristics or Improvement Strategies Of Various Nanocarriersmentioning
confidence: 86%